2015
DOI: 10.3389/fpsyg.2015.00192
|View full text |Cite|
|
Sign up to set email alerts
|

Bayesian reasoning with ifs and ands and ors

Abstract: The Bayesian approach to the psychology of reasoning generalizes binary logic, extending the binary concept of consistency to that of coherence, and allowing the study of deductive reasoning from uncertain premises. Studies in judgment and decision making have found that people’s probability judgments can fail to be coherent. We investigated people’s coherence further for judgments about conjunctions, disjunctions and conditionals, and asked whether their coherence would increase when they were given the expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 61 publications
8
68
0
Order By: Relevance
“…There is one-premise centering: inferring if A then B from the single premise AB. And two-premise centering: inferring if A then B from the two separate premises A and B. Centering is valid for quite a wide range of conditionals ( [19,20,66]). It is clearly valid for the material conditional, since not-A or B must be true when A and B is true.…”
Section: Centeringmentioning
confidence: 99%
“…There is one-premise centering: inferring if A then B from the single premise AB. And two-premise centering: inferring if A then B from the two separate premises A and B. Centering is valid for quite a wide range of conditionals ( [19,20,66]). It is clearly valid for the material conditional, since not-A or B must be true when A and B is true.…”
Section: Centeringmentioning
confidence: 99%
“…Conditionals of the sort, if A then B, for instance, do not correspond to the so-called material conditional of logic or to conditional probabilities (see also Byrne & Johnson-Laird, 2009;Schroyens, 2010). Probabilistic approaches to reasoning postulate that the probability calculus should replace logic, especially for conditionals, and that what matters is probabilistic validity (Adams, 1998)-p-validity, for short-which holds whenever a conclusion is no less probable than its premises given any consistent assignment of probabilities (e.g., Chater & Oaksford, 2009;Cruz, Baratgin, Oaksford, & Over, 2015;Evans, 2012;Oaksford & Chater, 2007;Over, 2009;Pfeifer, 2013;Pfeifer & Kleiter, 2009). A consequence of the model theory, however, is that probabilities are not part of the fundamental meanings of compound assertions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these coherent probability intervals for the conclusion are a deductive consequence of the premises and their probabilistic interpretation. It has been shown that peoples' assignments of conclusion probabilities respect probabilistic coherence (Cruz et al, 2015). This is not the same as…”
Section: Sl (P 5) Further Suggest That the Bayesian Probabilistic Apmentioning
confidence: 74%
“…Yet there is good evidence that people are a sensitive to this "blurred" notion (Cruz, Baratgin, Oaksford, & Over, 2015). According to a probabilistic account based on what Edgington (1995) called the Equation, that is, Pr(if p then q) = Pr(q|p), the probabilities of the premises of an inference place coherence constraints on the range of values that the probability of the conclusion can take.…”
Section: Sl (P 5) Further Suggest That the Bayesian Probabilistic Apmentioning
confidence: 99%